A narrative review of local ecological knowledge in urban water supply governance - Wibowo, Ganggas Prakosa Sigit (EcoVision: Journal of Environmental Solutions, 2026)
Background: According to the UN World Urban Prospect data, by 2050, 72.2% of the world’s population will live in cities, especially in Asia and Africa. Meanwhile, in Indonesia, the urban population is estimated to reach 70% of the total population by 2045. This indicates the presence of population pressures due to rapid urbanization and environmental stress in the form of increasing demand for clean water supply to sustain urban population growth. This study is a narrative review examining the implementation of Local Ecological Knowledge (LEK) as a grassroots approach in urban water management in Indonesia and other countries. Methods: Through analysis of 24 case studies using a narrative review approach from both developing and developed countries, this research aims to identify key factors enabling the application of LEK within an integrated bottom-up water resource management framework. Findings: Analysis reveals three critical patterns: successful LEK integration occurs when traditional systems operate within strong social structures with institutional recognition; failures emerge from power imbalances and technocratic-centralistic approaches; and urbanization threatens LEK continuity. Indonesian cases reveal LEK manifesting in spiritual-ecological relationships with water sources, collective cultural practices as social control mechanisms, and autonomous community-based management systems. Self-supply practices by approximately 90% of Indonesian urban households represent adaptive resilience rooted in LEK. Conclusion: This study demonstrates that LEK is a culturally embedded knowledge system essential for sustainable urban water governance. The primary challenge is misalignment between community logic and institutional logic, perpetuated by power imbalances and dominance of scientific-instrumental knowledge. Achieving sustainability requires collaborative platforms bridging formal and local knowledge systems, and capacity-building support for existing community practices. Novelty/Originality of this article: This study recommends a paradigm shift in water management from a predominantly technocratic-centralistic approach toward a hybrid planning model that recognizes LEK as a knowledge system that can be integrated into public policy frameworks.